Real Time Implementation of Digital Modulation Techniques on Warp FPGA - Bhardwaj, Lokesh (My University, 2010)
In wireless communication, a signal is modulated before it is transmitted. Modulation is superimposing of modulating signal over a high frequency carrier. The carrier is a sinusoidal signal with a very high frequency. Modulation is required so as to achieve easy radiation, achieving simultaneous transmission of several signals and the bandwidth of the transmitted signal can be increased for better transmission quality. Different modulation techniques are used such as M-PSK, M-QAM and M-DPSK. The M-ary modulation is done and the signals obtained after modulation are transmitted through the antenna associated with the transmitting radio board of WARTP board. These signals are then received by the antenna associated with receiving radio board. The generation of information bits and their modulation along with activation of modules of WARP FPGA such as radio boards, clocks and downloading of signals to be transmitted through the antenna are done through the program running offsite of the WARP FPGA board. WARP is Wireless Open Access Research Platform. The WARP board is equipped with the radio boards which are responsible for the processing of signals to be transmitted and received. The signals are modulated by different techniques for their transmission and bit error rate performances of these techniques are compared to show the best modulation technique among all. Theoretical bit error rates for M-PSK and M-QAM are evaluated using MGF approach. The information bits of 12000 length is taken and bit error rate is evaluated for the base band gain of range from 1 to 3. It can be seen that the BER for BPSK is least while it increases as order of modulation increases. However QAM shows slightly better performance than PSK due to its dual modulation standards. DPSK uses one and a half cycle of carrier wave in the single information bit. DPSK is simpler to implement than ordinary PSK since there is no need for the demodulator to have a copy of the reference signal to determine the exact phase of the received signal, however the probability of erroneous demodulation is greater in DPSK. The performance of these modulation techniques in real time makes the bit error rate to increase initially for all techniques; however it gets reduced with increase in the transmitter base band gain. Also demodulated signals in every case can be seen. The maximum distortion in demodulated signals can be seen in case of higher order modulation.
M.E. (ECED)
Keywords: Digital Modulation Techniques; FPGA